Simple ≠ fácil: investigación sobre el estilo y el lenguaje de el bajista Steve Swallow mediante un análisis de transcripciones, aplicado a un recital final - Cornejo Bermeo, Andrés Felipe (2021)
The goal of this study is to understand the language and style of the American bass player Steve Swallow. By focusing on his developments as a composer, accompanist and soloist, it is possible to understand Swallows musicianship as a whole. The research delves into Swallows creative and technical processes through the transcription and subsequent analysis of audible material. The studys findings examine a wide range of devices utilized by Swallow in the three facets of his career. Some of these devices are recurrent while others are not; nonetheless the findings provide interesting material for examination that can engage the reader with different perspectives on how to make music.